2013
DOI: 10.1002/14651858.cd009853.pub2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different methods of remuneration on the behaviour of primary care dentists

Abstract: The effect of different methods of remuneration on the behaviour of primary care dentists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 23 publications
2
92
0
5
Order By: Relevance
“…NHS GDPs are acutely sensitive to incentives within the remuneration system. 13,15,16,104 Retrospective payment systems like FFS commonly lead to overtreatment, 17,18,104 whereas prospective systems or 'per capita' payments often lead to undertreatment. 18 When incentives promote preventative activity, NHS GDPs tend to actively engage and shape their dental team accordingly, greatly increasing the use of role supplementation and substitution.…”
Section: Organisation Of Nhs Dentistry In Primary Carementioning
confidence: 99%
“…NHS GDPs are acutely sensitive to incentives within the remuneration system. 13,15,16,104 Retrospective payment systems like FFS commonly lead to overtreatment, 17,18,104 whereas prospective systems or 'per capita' payments often lead to undertreatment. 18 When incentives promote preventative activity, NHS GDPs tend to actively engage and shape their dental team accordingly, greatly increasing the use of role supplementation and substitution.…”
Section: Organisation Of Nhs Dentistry In Primary Carementioning
confidence: 99%
“…[49][50][51][52][53] The need for health system reform in order to support the application of enhanced skills in practice to improve patient care was identified with a continuous programme of training to be established rather than a one-off course.…”
Section: Professional Developmentmentioning
confidence: 99%
“…A Cochrane review 78 concluded that educational meetings had a small effect on professional practice and health outcomes but the effects were likely to be smaller still for complex behaviours. Both a systematic review of incentives to follow best practice in health care 79 and a Cochrane review of the effect of remuneration on primary care dentists' behaviour cited within it 27 concluded that financial incentives can have a 'modest' effect on improving the quality of health care.…”
Section: Stakeholder Perspectives Of the Blended/incentive-driven Sermentioning
confidence: 99%
“…27 The study design reported here has enabled a direct comparison of practices offering incentive-driven preventative dentistry with those offering traditional, solely activity-driven dentistry operating under the nGDS. This enhances early findings from the ongoing national dental contract pilots introduced following the Steele report 2 which have focused on patients' and practitioners' views of the new clinical pathway, reporting them to be strongly supportive.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation